Design, implementation, and interpretation of amplification studies for prion detection. Issue 2 (4th March 2018) - Haley, Nicholas J.; Richt, Jürgen A.; Davenport, Kristen A.; Henderson, Davin M.; Hoover, Edward A.; Manca, Matteo; Caughey, Byron; Marthaler, Douglas; Bartz, Jason; Gilch, Sabine
ABSTRACT: Amplification assays for transmissible spongiform encephalopathies have been in development for close to 15 years, with critical implications for the postmortem and antemortem diagnosis of human and animal prion diseases. Little has been published regarding the structured development, implementation and interpretation of experiments making use of protein misfolding cyclic amplification (PMCA) and real time quaking-induced conversion (RT-QuIC), and our goal with this Perspectives manuscript is to offer a framework which might allow for more efficient expansion of pilot studies into diagnostic trials in both human and animal subjects. This framework is made up of approaches common to diagnostic medicine, including a thorough understanding of analytical and diagnostic sensitivity and specificity, an a priori development of amplification strategy, and an effective experimental design. It is our hope that a structured framework for prion amplification assays will benefit not only experiments seeking to sensitively detect naturally-occurring cases of prion diseases and describe the pathogenesis of TSEs, but ultimately assist with future endeavors seeking to use these methods more broadly for other protein misfolding disorders, including Alzheimer's and Parkinson's disease.